Optimal Radio Access Network Selection in Multi-RAT HetNets Using Matching Game Approach - M. G. Anany; Eman Serag El Din; Mahmoud M. Elmesalawy (International Telecommunications Society (ITS), 2019)
Due to the dramatic growth in mobile data traffic, Multiple Radio Access Technologies (Multi-RAT) heterogeneous Networks (HetNets) have been proposed as a promising solution to cope with the high traffic demand in mobile networks. In this work we propose a User Equipment (UE) radio access network selection algorithm in a Wireless Local Area Network (WLAN) and LTE Multi-RAT HetNet, where matching game approach is applied. In this algorithm, UEs propose to their best candidate based on a utility function that is formulated to maximize their achieved downlink data rate. Then base stations accept or reject the proposals based on their utility. The performance of the proposed approach is investigated and compared to other models, and simulation results proved its outperformance.
Keywords: 330; Multi-RAT; HetNet; network selection; matching game